La conversione nella tradizione giuridica hindu: salvezza e comunità - Francavilla, Domenico (Convertirsi, de-convertirsi, riconvertirsi, 2016)
The article aims to highlight some issues concerning the complex question of conversion in Hindu law with reference to the Hindu conception of salvation and to the impact of conversion on the application of Hindu personal law in modern India. It also points out some of the many interactions between conversion and State policies based on caste, such as affirmative actions. The understanding of being part of a specific community and religious tradition emerges as a factor that connects soteriological and social aspects in the Hindu conception of conversion.